THE EFFECT OF STIRRING TECHNIQUES ON TiO2 NANOPARTICLE SIZE BY USINGA WET CHEMICAL METHOD - Yohanes E. Gunanto; K. Sinaga; Yustinus P. Pratala (Jurnal Sains Materi Indonesia, 2016)
THE EFFECT OF STIRRING TECHNIQUES ON TiO2 NANOPARTICLE SIZE BY USINGA WET CHEMICAL METHOD. The TiO2 nanoparticles were synthesized by a wet chemical method. The influence of stirring on the particle size was investigated. In the first technique, the stirring was done during the process of mixing, while in the second technique the stirring was done after the mixing process is finished. The particle size was characterised using XRD, TEM, and PSA, while the BET surface area used. The first technique, obtained a fairly small grain size of about 12-50 nm, while the second technique obtained particle sizes between 1300-1600 nm.